1998
DOI: 10.1007/s004050050038
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation as a successful rehabilitation for radiation-induced deafness

Abstract: Radiotherapy of the head and neck can be associated with conductive and/or sensori-neural hearing loss. We report the case of a 67-year-old man who developed complete bilateral deafness caused by labyrinthitis and radiation-induced neuritis of the acoustic nerve after postoperative radiotherapy of a nasopharyngeal carcinoma. Two years postoperatively extensive clinical workup including computed tomography and magnetic resonance imaging showed no recurrence or secondary brain tumors. To facilitate sound percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 17 publications
2
28
0
1
Order By: Relevance
“…In the current literature, there are only a handful of case reports and case series that suggest cochlear implantation as an effective rehabilitative tool in mitigating hearing loss in patients who received RT to the head and neck (4-7). These observations were consistent with the finding that the retro-cochlear pathways were functionally spared in modern day radiotherapy of head and neck cancers (1).…”
Section: Introductionmentioning
confidence: 99%
“…In the current literature, there are only a handful of case reports and case series that suggest cochlear implantation as an effective rehabilitative tool in mitigating hearing loss in patients who received RT to the head and neck (4-7). These observations were consistent with the finding that the retro-cochlear pathways were functionally spared in modern day radiotherapy of head and neck cancers (1).…”
Section: Introductionmentioning
confidence: 99%
“…Cochlear implants are effective when the auditory nerve is functionally intact. When treating nasopharyngeal carcinoma with RT, it has been reported that the retrocochlear pathway could remain intact despite the cochlea receiving greater than 60 Gy (Marangos et al 2000;Formanek et al 1998). Due to the risk of significant retrocochlear pathology after radiation damage, patients who receive high doses of radiation may be worse off than other deaf patients (Jereczek-Fossa et al 2003).…”
Section: Inner Earmentioning
confidence: 98%
“…Although radiotherapy and radiosurgery are no longer factors for primary exclusion from ABI trial, overall results are less favorable after previous radiation. After radiosurgery, patients with previously implanted devices obtained some environmental sound recognition, but never any open speech recognition, either with cochlear implants 16 or with ABIs.…”
Section: Nonresponder Statusmentioning
confidence: 99%